Pengaruh Ekspor, Impor dan Kurs Terhadap Cadangan Devisa Nasional Periode 1999-2010 - Juniantara, I Putu Kusuma; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 1, November 2012 (pp. 1-60), 2012)
A country that can not afford to meet the country's need to import from other countries and the countries that supply of certain commodities from other countries in need will tend to export activity. The title of this research is the influence of Import Export and Foreign Exchange Reserves Against National Period 1999-2010. The problem in this study is the import, export and exchange rate simultaneously significantly affect the national foreign exchange reserves? How does the influence of export, import and exchange rate partially on national reserves? Export the results of this study are a positive and significant impact on the national reserves. Imports are not significantly positive effect on the national reserves. Exchange rate has positive and significant impact on the national reserves.
Keywords: National Foreign Exchange , Export , Import , exchange rate